Stent-in-stent, a safe and effective technique to remove fully embedded esophageal metal stents: case series and literature review - Aiolfi, Alberto; Bona, Davide; Ceriani, Chiara; Porro, Matteo; Bonavina, Luigi (Endoscopy International Open, 2015)
Background: Endoscopic stenting is a widely used method for managing esophageal anastomotic leaks and perforations. Self-expanding metal stents (SEMSs) have proved effective in sealing these defects, with a lower rate of displacement than that of self-expanding plastic stents (SEPSs) as a result of tissue proliferation and granulation tissue ingrowth at the uncovered portion of the stent, which anchor the prosthesis to the esophageal wall. Removal of a fully embedded stent is challenging because of the risk of bleeding and tears.Materials and methods: Temporary placement of a new stent within the first stent (stent-in-stent technique) may facilitate the mobilization and safe removal of both stents by inducing pressure ischemia of the granulation tissue. We report our own experience with the stent-in-stent technique in five consecutive patients in whom a partially covered Ultraflex stent had previously been implanted and compare our results with those in the current literature.Results: The first SEMSs remained in place for a median of 40 days (range 18 – 68) without displacement. Placement of the new stent was technically successful in all patients. All stents were left in place for a median of 9 days. The overall stent-in-stent success rate was 100 % for the removal of embedded stents. No serious adverse events related to the procedure occurred. Conclusion: The procedure was safe, well tolerated, and effective. The use of a partially covered Ultraflex stent of the same size as the old stent for a limited time (≤ 6 days) was consistently successful.